The association between job stress related factors and job performance at Pejabat Mara Negeri Melaka / Hanisah Husin - Husin, Hanisah (Faculty of Office Management and Technology, 2018)
This study is conducted in order to examine the association of job stress related factors and employee job performance at Pejabat MARA Negeri Melaka. The main focus of this study was to identify the main factor that can influence job performance by examining the factors, including role ambiguity, workload and role conflict that can affect employee job performance at the organization. It also focusses to establish the relationship between job stress related factors and job performance. This study adopted a descriptive research as a research design and employed a quantitative technique that carried out on 52 respondents, and the data are collected through a set of questionnaires. The study findings revealed that all the respondents had ever experienced stress from work and pointing out from the three job stress related factors which is role ambiguity, workload, and role conflict, only role ambiguity and role conflict are mainly affected their job performance on that organization. Therefore, the study concludes that two factors of job stress, which is role ambiguity and role conflict has a positive relationship to the employee’s job performance, which the more the stress, the less the employee will perform. While for workload, it can be concluded that the factor are not influencing performance because has negative correlation with job performance. The study recommends that employees should clearly define their roles and objectives in order to minimize role ambiguity and role conflict which can lead to poorer performance in an organization.